Development and validation of a predictive nomogram for lower extremity deep vein thrombosis dislodgement in orthopedic patients - Li, Zongxuan; Liu, Xiangdong; Li, Liang; Cao, Pengkai; Zhang, Guanyu; Jiao, Zhipeng; Wang, Fengkai; Hao, Qingchun; Li, Yunsong; Zhang, Yanrong (Frontiers in Surgery, 2023)
Objective: To analyze the risk factors of lower extremity deep venous thrombosis (DVT) detachment in orthopedic patients, and to establish a risk nomogram prediction model. Methods: The clinical data of 334 patients with orthopedic DVT admitted to the Third Hospital of Hebei Medical University from January 2020 to July 2021 were retrospectively analyzed. Logistic regression was used to perform univariate and multivariate analysis on the possible factors of thrombosis detachment, screen out independent risk factors, establish a risk nomogram prediction model by variables, and internally verify the predictability and accuracy of the model. Results: Binary logistic regression analysis showed that Short time window filter (OR=5.401, 95%CI = 2.338-12.478), lower extremity operation (OR=3.565, 95%CI = 1.553-8.184), use of tourniquet (OR=3.871, 95%CI = 1.733-8.651), non-strict immobilization (OR=3.207, 95%CI = 1.387-7.413), non-standardized anticoagulation (OR=4.406, 95%CI = 1.868-10.390), distal deep vein thrombosis (OR=2.212,95%) CI= 1.047-4.671) were independent risk factors for lower extremity DVT detachment in orthopedic patients (P<0.05). Based on these six factors, a prediction model for the risk of lower extremity DVT detachment in orthopedic patients was established, and the risk prediction ability of the model was verified. The C-index of the nomogram model was 0.870(95%CI: 0.822-0.919). The results indicate that the risk nomogram model has good accuracy in predicting the loss of deep venous thrombosis in orthopedic patients. Conclusion: The nomogram risk prediction model based on six clinical factors, including filter window type, operation condition, tourniquet use, braking condition, anticoagulation condition, and thrombosis range, has good predictive performance.